India’s Nuclear Policy - Sharma, Madhubala (International Journal of Psychosocial Rehabilitation, 2011)
Nuclear cooperation has brought a new dimension to India’s diplomacy in the 21st century. India’s status as a responsible nuclear power is predicated upon the civil relationships in the nuclear domain that it has established with major powers. This, despite not being a signatory to the Non-Proliferation Treaty and operating outside the ambit of the Nuclear Suppliers Group. This brief analyses the impact of key agreements with different countries on India’s engagements on the bilateral and multilateral level. It looks into the challenges facing the country in the implementation of these agreements and outlines the way forward for similar accords in the future.